Malaysian students’ perceptions of writing strategy in French language learning: A quantitative approach - Abdul Halim, Hazlina; Abd Rahim, Normaliza; Abdul Jabar, Mohd Azidan; Abdul Aziz, Adi Yasran (The International Journal of the Humanities, 2009)
This exploratory study aims to analyse Malaysian students’ perceptions of the types of strategy used in learning French as a foreign language with regard to writing skills. The study utilized quantitative method of data collection, by applying Dörnyei’s (1995) communication strategies taxonomy to the writing strategies. A total of 50 subjects participated in this study after their 100 hours of learning French. The task consisted of the administration of the writing task by the subjects. The instrument used in the study is a 2 part questionnaire consisting of 19 items.